Sistem Pakar Berbasis Web Untuk Menganalisa Gangguan Kejiwaan dengan Metode Fuzzy Mamdani - T Irfan Fajri, Zakial Vikki, Chaeroen Niesa (LPPM-UNIKI, 2021)
Research on this diagnosis is carried out in cases of mental disorders where to ensure a healthy human mind, it isnecessary to have a system that can handle it. To overcome this, an expert system was designed to facilitate patients indiagnosing mental disorders. The PHP & MySQL web-based system makes it easy to diagnose by selecting the symptomsthat may be experienced by the patient and the system will provide decision results based on the Mamdani fuzzy method.The result of the decision is the type of disease and the solution for it. Types of psychiatric disorders that can bediagnosed such as schizophrenia, bipolar disorder, psychopathy, obsessive compulsive disorder, schizoaffective,anorexia nervosa, multiple identity disorder, self harm/self injures, homosexsual and antisocial personality disorder.